Hearing Preservation After Cochlear Implantation May Improve Long-term Word Perception in the Electric-only Condition. Issue 9 (October 2016) - Dalbert, Adrian; Huber, Alexander; Baumann, Naemi; Veraguth, Dorothe; Roosli, Christof; Pfiffner, Flurin
Abstract : Objective: To correlate hearing preservation with word perception in the electric-only condition in recipients of full length cochlear implant (CI) electrode arrays. Study Design: Retrospective chart review. Setting: Tertiary academic referral center. Patients: CI recipients between January 2003 and December 2013 who had measurable residual acoustic hearing before surgery and serial postoperative word perception tests. Intervention: Demographic data, pre- and postoperative pure-tone average, and postoperative monosyllabic word perception scores were evaluated. Main Outcome Measure: Hearing preservation was correlated with postoperative monosyllabic word perception scores. Results: Data from 96 ears in 91 subjects were included. Complete or partial hearing preservation was achieved in 48%. After 6 and 12 months, no significant difference in word perception was found between subjects with and without hearing preservation. However, after 18 or more months, subjects with hearing preservation had significantly better word perception scores (83% versus 72%, p <0.05). Conclusion: Preservation of residual hearing leads to better word perception in the electric-only condition over the long term. CI recipients with hearing preservation continue to make progress after more than 12 months of CI experience whereas those without plateau at 12 months.